Dhiyaurrahman Danial, son of government pensioner receives Heitech Excellence Award - Siti Nurfarmy, Ibrahim (UMPSA, 2023)
GAMBANG, 21 October 2023 - The son of a retired government couple, Danial Mamat, 61 and Nor@Roshayati Hasan, 61 did not expect to receive the Heitech Excellence Award at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) 18th Convocation Ceremony today.